Egypt 1919 : the Revolution in literature and film - Ḥishmat, Dīnā (Edinburgh studies in modern Arabic literature., 2020)
The 1919 anti-colonial revolution is a key moment in modern Egyptian history and a historical reference point in Egyptian culture through the century. Dina Heshmat argues that literature and film have played a central role in the making of its memory. She highlights the processes of remembering and forgetting that have contributed to shaping a dominant imaginary about 1919 in Egypt, coined by successive political and cultural elites. As she seeks to understand how and why so many voices have been relegated to the margins, she reinserts elements of the different representations into the dominant narrative. This opens up a new perspective on the legacy of 1919 in Egypt, inviting readers to meet the marginalised voices of the revolution and to reconnect with its layered emotional fabric.--